Trabecular Hyalinizing Adenoma of the Thyroid (HAT) : A report of two cases (2016)
ABSTRACT The hyalinizing trabecular adenoma is a rare lesion of the thyroid. There is controversy in the literature about the correct name for this disease. Dr. Carney defended the benign nature of this condition and therefore continues calling it adenoma, the World Health Organization calls for the potential of tumor malignancy, and others qualify it as a variant of papillary carcinoma based on the presence of rearranged in transformation/papillary thyroid carcinoma (RET/PTC) rearrangements. In Latin America there are few reported cases. Two cases of hyalinizing trabecular adenoma are reported. The first is a 40-year-old woman with a thyroid nodule of 3 x 3 cm. The immunohistochemistry was positive for thyroglobulin and calcitonin and negative for cytokeratin 19 and chromogranin. The second case is a 36-year-old patient with a thyroid nodule of 4 x 4 cm with an immunohistochemical pattern identical to the first case. Trabecular hyalinizing adenoma is a benign disease, easily confused with papillary or medullary thyroid carcinoma. Awareness of this entity will allow a better classification and management of thyroid conditions.